Estudo da extração líquido-líquido para o processo de purificação de biodiesel metílico - Pinheiro, Regiane Silva (2013)
In the process of purification of biodiesel is of extreme importance washing methyl or ethyl ester rich- phase, since in conventional processes there is a great amount of water. During the washing is extracted primarily excess alcohol. Composition data for the washing process of biodiesel is still scarce in the literature and the study of liquid-liquid equilibrium provides the means to develop equipment and to optimize the extraction processes. Thus the main goal of this work is to determine equilibrium data for three different ternary systems: water - methanol - soybean biodiesel; corn biodiesel – methanol – water; methanol - coconut biodiesel - water at 20 ° C and 40 ° C. The experiments were carried out in equilibrium cells where the temperature was kept constant by thermostat control. The experimental determination was made by the method of densimetry. The consistency of data obtained for the tie lines was verified by correlations. It was verified by the ternary graphs, little influence of temperature on the systems studied. The equilibrium data were correlated liquid-liquid models for the activity coefficient NRTL, UNIQUAC and UNIFAC and proved quite satisfactory